Oncology nurses' demographics, personal factors and length of years in services to their level of depression - Milan, Mark Jason; Paggabao, Ernest Matthew; Pagtiilan, Gary.; Pajimna, Janine Audrei; Pangan, Edselle .; Punzalan, Bermon Wren.; Salivio, Daniel John.; Sim, Mikaela Angela .; Sison, Paulo Ross.; Virtudazo, Jessa Mae. (Manila College of Nursing University of the Philippines Manila, 2013)
Depression among the health care providers is becoming one of the emerging issues in the field of health care. This research employed a descriptive prevalence design to illustrate the oncology nurses currently employed in the UP-PGH Cl in terms of their levels of depression, years in service, demographics, and personal factors, specifically attitude towards death, religion, and experiences with death and cancer. Findings reveal that 13.3% of the population (n=15) has mild mood disturbance and around 60% of these nurses, a majority, has a dominant approach acceptance attitude toward death. There is also a slight difference between the numbers of units who have a death experience, 53.3%, to those who do not have, 46.7%. Knowledge of these figures is indispensable in reducing the incidence of depression among the staff to increase productivity through debriefing sessions.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, 2013.
Keywords: Nursing -- Research